Teaching Practicum Current Practices: Challenges and Opportunity - Shalawati Shalawati; Sitti Hadijah (UIR Press, 2018)
The aims of this study is to explore the practicum implementation in order to see barrier occurs and to suggest off possible solution to issues occur into the below specific objectives: (a) to explore form of PPL implementation from several points of view: school partners, supervisor-lecturer, and teacher-student, (b) to overview the actual work of the students in the school, viewing from workload and timing, (c) to describe supervision from school partner teacher, types of supervision and partnership pattern in the classroom. The approaches employed samples from four schools, a university and related research participants all of whom are probed for detail individual and group interview. There is also a look for document review applied for better comprehension of the practice. The selected schools are; two SMPs and two SMAs, all of which lie in Pekanbaru. Then, the university reviewed at was Universitas Islam Riau. The research sees that the currect practice is running well, however, there are few wrong doing happening on the ground that school management and PPL unit need to review about, such as workload of the students, supervision, and illegal request from schools that related to financial or non-financial. The timing of the practicum variation need some unified approached and the university need to delegate supervisor-lecturer for initial talk with schools regarding the timing, at about 2 months period. On the other hand, the preparation of the students is in need of revision in term of their self awarenes for experience-based learning. And post practicum reflection process is strongly suggested for better practice and indivdual strengthening learning process.